ANALYSIS OF WORKING HOURS AND WORKLOAD ON WORK PRODUCTIVITY WITH JOB SATISFACTION AS A MODERATING VARIABLE AT PT PLN BINJAI CITY CUSTOMER SERVICE UNIT - Heryanto Siburian; Mesra B; Elfitra Desy Surya (RADJA PUBLIKA, 2025)
This study aims to analyze the effect of working hours and workload on work productivity with job satisfaction as a moderating variable at PT PLN Binjai Kota Customer Service Unit. The research method used is a quantitative approach with Partial Least Square (PLS) analysis technique. The study population was all employees of ULP Binjai Kota, with a sample of 83 respondents. The results showed that working hours had a positive and significant effect on work productivity, while workload had a negative and significant effect on work productivity. In addition, job satisfaction was proven to have a positive and significant effect on work productivity and moderated the relationship between working hours and workload with work productivity. The R Square value of 0.836 indicates that the variables of working hours, workload, and job satisfaction are able to explain the variable of work productivity by 83.6%. These findings are expected to be managerial considerations in managing working hours and workload to improve employee satisfaction and productivity within PT PLN ULP Binjai Kota.